2013
DOI: 10.15191/nwajom.2013.0113
|View full text |Cite
|
Sign up to set email alerts
|

Multi-sensor examination of hail damage swaths for near real-time applications and assessment

Abstract: Severe thunderstorms occurred across portions of South Dakota, Nebraska, Iowa, and Missouri on 18 August 2011, resulting in several swaths of large hail that caused significant damage to crops toward the end of the growing season. Changes with time in the normalized difference vegetation index (NDVI) and truecolor imagery from the Moderate Resolution Imaging Spectroradiometer instrument aboard the National Aeronautics and Space Administration's Terra satellite identify the damaged area, with corroboration by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 14 publications
3
18
0
Order By: Relevance
“…Molthan et al performed a similar analysis as Gallo et al (2012) but also incorporated observations with higher spatial resolutions from addi-tional earth-observing instruments, including Landsat-7 Enhanced Thematic Mapper Plus (30-m spatial resolution), Terra Advanced Spaceborne Thermal Emission and Radiometer (15 m), Système Pour l'Observation de la Terre-4 (SPOT-4, 20 m), and SPOT-5 (10 m). Molthan et al (2013) obtained similar results to those of Gallo et al (2012) with respect to the correlations between NDVI change and maximum estimated size of hail (MESH) size. Molthan et al (2013) used the higher spatial resolution sensors to confirm fieldscale damage and NDVI reductions in areas that corresponded to the MESH hail-fall streaks and coarserresolution MODIS observations.…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…Molthan et al performed a similar analysis as Gallo et al (2012) but also incorporated observations with higher spatial resolutions from addi-tional earth-observing instruments, including Landsat-7 Enhanced Thematic Mapper Plus (30-m spatial resolution), Terra Advanced Spaceborne Thermal Emission and Radiometer (15 m), Système Pour l'Observation de la Terre-4 (SPOT-4, 20 m), and SPOT-5 (10 m). Molthan et al (2013) obtained similar results to those of Gallo et al (2012) with respect to the correlations between NDVI change and maximum estimated size of hail (MESH) size. Molthan et al (2013) used the higher spatial resolution sensors to confirm fieldscale damage and NDVI reductions in areas that corresponded to the MESH hail-fall streaks and coarserresolution MODIS observations.…”
Section: Introductionsupporting
confidence: 66%
“…Molthan et al (2013) obtained similar results to those of Gallo et al (2012) with respect to the correlations between NDVI change and maximum estimated size of hail (MESH) size. Molthan et al (2013) used the higher spatial resolution sensors to confirm fieldscale damage and NDVI reductions in areas that corresponded to the MESH hail-fall streaks and coarserresolution MODIS observations. This study builds on previous work by comparing damage identified by NDVI change (thresholding) and an image-processing technique (anomaly detection) to identify areas of hail damage in Aqua MODIS imagery.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations